Nanoparticles Modulating the Immune Microenvironment in Breast Cancer Treatment - Guo LJ; Wu J; Lu W; Li J; Wang Y; Yang H; Wang TZ (International Journal of Nanomedicine)
Li-Juan Guo,1 Jinsheng Wu,1 Weifeng Lu,2 Jing Li,1 Yeling Wang,1 Hui Yang,1 Tian-Zhu Wang3 1Department of Radiotherapy, The First Affiliated Hospital of Hainan Medical University, Haikou, 570102, People’s Republic of China; 2Institute of Oncology, The First Affiliated Hospital of Hainan Medical College Institute of Oncology, Haikou, 570102, People’s Republic of China; 3Department of Radiation Oncology, Hainan Cancer Hospital, Haikou, 570311, People’s Republic of ChinaCorrespondence: Tian-Zhu Wang, Department of Radiation Oncology, Hainan Cancer Hospital, Haikou, 570311, People’s Republic of China, Email pillarsky@126.comAbstract: Breast cancer remains a significant therapeutic challenge, with the immune microenvironment playing a crucial role in its progression and treatment response. This review investigates the potential of nanoparticles to modulate the immune microenvironment in breast cancer therapy. Initially, we discuss the composition and influence of the immune microenvironment on breast cancer, followed by current strategies targeting these components. We then provide strategies of nanoparticles for targeting immune cells such as macrophages, dendritic cells, and T-cells. The role of nanoparticles in enhancing immune checkpoint blockade (ICB) and their application in cancer vaccines is also examined. Additionally, we explore the synergistic effects of combining nanoparticles with conventional therapies. The review addresses the challenges in clinical translation, focusing on safety, biocompatibility, and toxicity. Finally, we outline future research directions and the potential advancements in nanoparticle-based immunotherapy, emphasizing their transformative impact on breast cancer treatment.Keywords: nanoparticle, breast cancer, immune cells